2005
DOI: 10.1007/s0330-005-0032-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of bone-subtraction CT angiography (BSCTA) in head and neck imaging

Abstract: Fifty-one patients were examined with bone subtraction CT angiography (BSCTA). Data were acquired on 4-and 64-slice spiral CT systems. The post-processing method is based on fully automatic registration of non-enhanced and contrast-enhanced CT data and subsequent selective bone removal. Vascular structures and brain tissue are retained with the original CTA noise level. Image quality and delineation of the pathologic process were assessed and artifacts introduced by the bone removal process recorded. The bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 30 publications
2
48
0
Order By: Relevance
“…17,21 Bone-subtraction CTA 22,23 has been developed to overcome this problem. A feasibility study 22 and a study with 100 patients 24 showed that BSCTA can improve the detection of vascular pathology closely adjacent to bony structures.…”
Section: Discussionmentioning
confidence: 99%
“…17,21 Bone-subtraction CTA 22,23 has been developed to overcome this problem. A feasibility study 22 and a study with 100 patients 24 showed that BSCTA can improve the detection of vascular pathology closely adjacent to bony structures.…”
Section: Discussionmentioning
confidence: 99%
“…16 After registration, an initial bone mask is defined in the NECT volume by thresholding; the bone mask is tentatively expanded in 3D by morphologic dilation. 10 To reduce the risk of artificial vessel lumen reduction, we determined the optimal contact interface between vessels and bone adaptively. In the absence of vessels, the bone mask is kept expanded and the corresponding voxels are set to a CT value of Ϫ1024 HU; in areas of bonevessel contact, the corresponding NECT voxels are locally subtracted.…”
Section: Bone Subtractionmentioning
confidence: 99%
“…To eliminate voxels representing bone or calcification in the final image and prevent them from possibly obscuring the visualization of vessels, one may apply bone-subtraction techniques. Bone-subtraction CTA (BSCTA), using a (low-dose) nonenhanced scan to create a bone model, which then is subtracted from the CTA data, [10][11][12][13] has proved to be a robust method, which can be fully automated, requiring no user interaction. This technique has been shown to be beneficial in a variety of clinical settings.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In meningiomas fed by a single internal or external carotid artery, DSA imaging clearly reveals the staining and arteriovenous branches of the tumor, but those fed by both an internal and external carotid artery cannot be displayed well as the image does not show both sides simultaneously. Multi-slice spiral CT vascular imaging involves a contrast injection to the full arterial and venous phases to fully stain the tumor and display dual feeding arteries and reflux veins, and has received attention from a number of researchers (3,5,6). To understand the advantages and disadvantages of multi-slice CT angiography (MSCTA) and DSA in the angiography of meningiomas, a comparative study of the two methods in the detection of meningioma blood supply was performed.…”
Section: Introductionmentioning
confidence: 99%